Genomics of Salmonella contaminating backyard production systems reveals persistence and transmission of genetically related Salmonella on a farm basis. (27th September 2018) - Toro, Magaly; Rivera, Dácil; Toledo, Viviana; Campos‐Vargas, Reinaldo; Allard, Marc W.; Hamilton‐West, Christopher; Moreno‐Switt, Andrea I.
Abstract: Animals raised in backyard productive systems (BPS) have been frequently associated with Salmonella outbreaks. Several serovars have caused these events, showing that different BPSs can be contaminated by distinct Salmonella serovars. The aim of this study was to characterize the genomic diversity of Salmonella isolates obtained from BPSs in Central Chile to understand their genomic relatedness. A whole‐genome SNP‐based phylogenetic analysis of 22 Salmonella isolates from 12 locations revealed that S. Typhimurium isolates clustered based on the BPS that they were originally isolated from, and the same was established for S . Enteritidis isolates. Furthermore, our genomic analysis shows that animals from different species (i.e., a chicken, a duck and a pig) carried genetically related S. Typhimurium strains within the same BPS. Moreover, some of these genetically related isolates were obtained in different years (2013 and 2014), indicating that farm‐specific Salmonella can persist in BPSs for multiple years and that interspecies transmission is plausible in this environment. Understanding the dynamics of interspecies transmission of Salmonella serovars within a contaminated BPS is fundamental to the design of mitigation strategies to reduce outbreaks of human Salmonella associated with backyard production systems.